Reliability comparison between different 400 kV substation designs - Vikesjö, Johnny (My University, 2008)
This thesis examines how the unavailability for OKG will be affected by the planned replacement of the 400 kV substation at Simpevarp. The evaluation has been based on calculation of unavailability due to both faults and maintenance, fault and maintenance frequencies and estimated costs for the different substation designs. Four different variations of two-breaker arrangement designs have been simulated and been compared to simulations of the existing substation. To perform the calculations a program has been developed in java that simulates the different substation designs. The fault probabilities used in this study has primarily been taken from fault statistics for the Swedish grid but has also been compared to the assumptions used in other substation reliability studies. The results of this thesis show that the unavailability is likely to be higher for the proposed twobreaker arrangement design without separate disconnectors compared to the existing substation. When the two-breaker arrangement simulation instead included separate disconnectors the unavailability was found to be lower for the two-breaker arrangement design compared to the existing substation. The study also showed that the two-breaker arrangement designs had considerably lower fault frequencies compared to the existing substation. The thesis found that the unavailability that will be caused by maintenance can be significant and are likely to be higher than the unavailability caused by faults. The amount of unavailability caused by maintenance was, however, found to be uncertain because a large part of it can be performed during planned outage. Furthermore, it was found that the two-breaker arrangement design with and without disconnectors had similar expected present value of costs if the maintenance costs were excluded. This indicates that the best substation option from an economic point of view is determined by the maintenance costs.
Keywords: Elkraftteknik; Electric power engineering